Perception of Academic and Administrative Leaders at King Saud University towards Sustainable Development (The Arab Journal of Administration, 2026)
In light of the importance of sustainable development in promoting the progress of countries and communities at both the local and international levels and considering the effective role of universities in Saudi Arabia in achieving sustainable development, this study aimed to measure the perception of academic and administrative leaders at King Saud University regarding sustainable development. Additionally, the study sought to identify their opinions regarding the obstacles to achieving sustainable development and the key-ways to overcome them.This study followed a descriptive survey research method, and a questionnaire was used as a data collection tool. The study sample consisted of 192 individuals. The study yielded several results, including a high degree of awareness among the study sample regarding the goals of sustainable development. It was found that individuals with PhD and academic leaders had the highest level of awareness of the concept of sustainable development. The study also revealed that administrative obstacles were among the major hindrances that could limit the perception of academic leaders regarding sustainable development at King Saud University.Based on the study’s results, several recommendations were made, including the importance of continuing to provide appropriate financial resources to incentivize academic and administrative leaders in promoting sustainable development. Additionally, directing media channels to actively promote topics related to sustainable development and raise awareness of its goals was emphasized. Furthermore, linking promotion systems to achievements and the implementation of sustainable development was recommended.